Research on Mesoscopic Response of Asphalt Pavement Structure under Vibration Load - Zhanyou Yan; Enli Chen; Zhen Wang; Chundi Si (Shock and Vibration)
The various damages of asphalt pavement are closely related to the mesomechanical gradual behavior of asphalt materials, and it is very important to study the mesoscopic response under vibration loading in order to reveal the failure mechanism of asphalt pavement. The semisinusoidal vertical load is applied to the subgrade-surface discrete element model in this paper, and we use the model to analyze the evolution behavior of microcrack generation and expansion processes, stress distribution and stress transfer, and displacement field in various structural layers of asphalt pavement. The results show that the number of cracks increases rapidly on both sides of the vibration load, the rut is generated due to repeated load on the wheel, the asphalt mixture has bulging phenomenon on both sides of the rut and formed macroscopic cracks at the ridge, the microcracks extend mainly along the weak joints of the edges of the coarse aggregate and the asphalt cement, the number of microcracks increases slowly at the initial stage of the vibration load, the microcracks increase sharply until macroscopic cracks appear with the vibration load increases, the direction of compressive stress extends parallel to the microcrack, and the direction of tensile stress extends perpendicular to the microcracks inside the asphalt pavement. The results show that the discrete element method can not only obtain the stress and displacement of each structural layer, but also reveal the microcrack gradual behavior between particle flows.